Metagenomic Insights into How Understory Vegetation Enhances Soil Nitrogen Availability via Microbial Nitrogen Transformation in Poplar Plantations - Wenyu Jia; Tong Li; Peilei Ye; Yuxin Chen; Ruoning Zhu; Ruixin Yan; Haoran Yue; Ye Tian (Agronomy)
Long-term monoculture of poplar plantations for industrial material production has been widely reported to cause severe soil degradation, while the presence of understory vegetation might enhance soil nitrogen (N) transformation and supply. This study employed a field experiment using a randomized block design with three blocks and four understory treatments, including understory removal, N-fixing species planting, single-species retention, and diverse vegetation retention, in poplar plantations on a mid-latitude alluvial plain in China over 6 years to assess the effects of different species and richness of understory on soil N transformation and related microbial traits via 15N assays and shotgun metagenomics. The results showed that understory removal significantly reduced soil N transformation rates, bacterial abundance, and gene abundance associated with N transformation. Compared to a single-species understory, retaining a diverse understory with high species richness significantly increased soil gross N transformation rate of mineralization by 149%, nitrification by 221%, and immobilization by 85%; comprehensively enriched dominant bacterial phyla; and elevated gene abundances of gdh_K15371, ureB, hao, and amoA_B associated with N transformation. No significant difference in N transformation rates existed between N-fixing species planting treatment and single-species retention treatment, while N-fixing species planting treatment specifically promoted the soil bacterial phyla Nitrospirae and Chloroflexi, and increased the gene abundances of gdh_K15371 and hao. These findings demonstrate that both introducing N-fixing species and an increase in species richness of the understory effectively promoted soil N transformation but that different underlying mechanisms existed. Planting N-fixing species selectively increased the soil bacterial phyla of Nitrospirae and Chloroflexi, whereas the increase in species richness broadly enriched soil bacterial diversity, thereby inducing the enrichment of the functional genes and enhancing soil N transformation. In conclusion, both planting N-fixing species and retaining diverse understory vegetation were effective strategies for maintaining sustainable management of poplar plantations by increasing soil N availability.